Analysis Of The Business Development Plan For Gambir Products Using The Canvas Model - Sitakar, Beny; Nurhayati, Nurhayati; Dharma, Budi (UNIVERSITAS PAKUAN, 2020)
The purpose of this study is to analyze the design of gambir product business development using the canvas model, with a focus on identifying and analyzing the main components in the canvas business model that can be applied to the development of gambir product business, formulating appropriate business development strategies to increase the competitiveness of gambir products in the market and providing recommendations for sustainable gambir product business development based on canvas business model analysis. This study uses a qualitative descriptive research method that is used so that researchers can explain more deeply and comprehensively about the description of the case that occurred in the field. Data collection methods by observation, interviews and documentation of gambir farmers in Bongkaras village, Silima Pungga-Pungga district, Dairi district, North Sumatra Province. The results of the Gambir product business research in Bongkaras village were found to have covered all the key elements of the Business Model Canvas (BMC) to increase competitiveness. However, additions were made for improvements to several elements of the Canvas Model such as Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure